A new pygmy sundew, Drosera Albonotata (droseraceae), from the western wheatbelt and an updated diagnostic key to the orange-flowered pygmy Drosera of Western Australia - Robinson, A.; Cross, Adam; Meisterl, M.; Fleischmann, A. (2018)
A new species of Drosera-Drosera albonotata-from the western Wheatbelt (Western Australia) is described and illustrated. The taxon, which is largely restricted to sandy clay loam soils in Wandoo woodland and shrubland, is morphologically similar to D. miniata and D. coomallo but can be distinguished by its distinct floral features and ecology. A distribution map of the new species and its allies and a revised and updated diagnostic key to the twelve recognised orange-flowered pygmy Drosera in Western Australia are provided.